Political redistribution: The role of delegated lobbying and wage bargaining - Hans Peter Grüner (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
Traditional political economy models of taxation fail to explain why there is so little redistribution of wealth despite significant wealth inequalites. This is for two reasons: (1) The median voter approach cannot deal with a multidimensional policy-space and (2) wealth taxation affects well-organized and homogenous interest groups so that lobbying affects policy outcomes. In this paper the interaction of factor price bargaining and delegated tax-lobbying is studied. Two agents engage in lobbying: managers of large firms and trade union leaders. Low wealth taxation is the natural consequence of income maxmimization on the side of interest group leaders if (1) managers are in a position to appropriate part of the firms' revenues for themselves and (2) union members cannot monitor the lobbying activities of union leaders.
Keywords: D31; D72; 330; Lobbying; taxation of wealth; wage bargaining; Vermögensteuer; Vermögenspolitik; Interessenpolitik; Verhandlungstheorie des Lohnes; Theorie